2010
DOI: 10.1177/096739111001800702
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Apparatus for Measurement of Elongational Flow Properties for LDPE Melt and the Effect of Testing Conditions

Abstract: An experimental rig was designed and constructed for melt strength measurement and was assembled at the end of a single screw extruder used for the production of low-density polyethylene (LDPE) melt. The experimental rig was coupled with a high speed data logging system and a personal computer for the real-time measurement of melt strength. The molten LDPE was extruded through a capillary die, forming a continuous filament before being pulled down by speed-adjustable mechanical rollers until the filament faile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…For any given roller speed, the drawdown force increased with increasing volumetric flow rate in the extruder from 1.4 × 10 −7 to 4.1 × 10 −7 m 3 /s. This observation was in line with the work of Gupta and Bhattacharya [9] and our previous work [5, 29]. Higher volumetric flow rate was referred to as greater energy input or storage in the deformable polymer melts.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…For any given roller speed, the drawdown force increased with increasing volumetric flow rate in the extruder from 1.4 × 10 −7 to 4.1 × 10 −7 m 3 /s. This observation was in line with the work of Gupta and Bhattacharya [9] and our previous work [5, 29]. Higher volumetric flow rate was referred to as greater energy input or storage in the deformable polymer melts.…”
Section: Resultssupporting
confidence: 90%
“…As for the effect of volumetric flow rate from the extruder, it was found that the roller speed to failure for neat LDPE and wood/LDPE composites changed with changing volumetric flow rate. Higher volumetric flow rate contributed to greater average drawdown force and drawdown time because of the greater energy inputs given from the extruder [5, 29]. This behavior and its explanation are similar to those given for the LLDPE/LDPE blend system.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Figure 3 illustrates an experimental arrangement for melt strength measurement of the coextruded LDPE which used the coextrusion rig from Figure 1 coupled with an extension of the melt strength measuring unit, roller take‐up device, visualization devices, and temperature control equipment. The experimental set‐up and factions of these components were already detailed and given in previous works 10, 11. The drawdown force ( F ) as a function of time was required for accurate measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The most widely used and important device for the melt strength and transient extensional viscosity measurements is so‐called “Rheotens” 7–9. Recently published works by Sombatsompop et al10–12 proposed an experimental device which was specially designed and constructed in a similar fashion to the Rheotens to determine the melt strength online in a single screw extruder using a wide range of polymer systems including homopolymers,10, 11 polymer blends and composites12 and processing and reprocessing conditions 10, 11. They suggested that the drawdown force of molten LDPE was dependent on volumetric flow rate, die temperature, roller speed, take‐up style, and the number of extrusion passes.…”
Section: Introductionmentioning
confidence: 99%